China's Belt and Road investment governance: building a hybrid model - Mark Feldman (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2019)
If designed and implemented as an effective and sustainable hybrid model, investment governance under China's Belt and Road Initiative could contribute greatly to its success. Striking an appropriate balance between the ambition of a state-driven model and the inclusiveness of a transnational policy network model will be of central importance.
Keywords: 330